Association Analysis of Nuclear Receptor Rev-erb Alpha Gene (NR1D1) and Japanese Methamphetamine Dependence - Kishi, Taro (Bentham Science Publishers Ltd, 2011)
Several investigations suggested abnormalities in circadian rhythms are related to the pathophysiology of psychiatric disorders, including drug addiction. Recently, orphan nuclear receptor rev-erb alpha and glycogen synthase kinase-3 β (GSK-3β) were shown to be important circadian components. In addition, the orphan nuclear receptor rev-erb alpha is a key negative feedback regulator of the circadian clock. These evidences indicate that rev-erb alpha gene (NR1D1) is a good candidate gene for the pathogenesis of methamphetamine dependence. To evaluate the association between NR1D1 and methamphetamine dependence, we conducted a case-control study of Japanese samples (215 methamphetamine dependence and 232 controls) with three tagging SNPs selected by HapMap database. Written informed consent was obtained from each subject. This study was approved by the ethics committees at Fujita Health University, Nagoya University Graduate School of Medicine and each participating member of the Institute of the Japanese Genetics Initiative for Drug Abuse (JGIDA). We did not detect an association between NR1D1 and Japanese methamphetamine dependence patients in allele/genotype-wise analysis, or the haplotype analysis. Our findings suggest that NR1D1 does not play a major role in the pathophysiology of methamphetamine dependence in the Japanese population.